Acessibilidade na TV 3.0 Brasileira a partir de mídias de legenda, glosa e áudio descrição - Costa, Richelieu R. A.; Omaia, Derzu; Araújo, Tiago M. U.; Pereira, Jóison O.; Coutinho, Anderson S.; Cruz, Miguel P. S.; Pontes, Victoria M.; Barbosa, Matheus M.; Silva, Abner S.; L. S. Filho, Guido (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2023)
The TV 3.0 project is under development, managed by the Forum of the Brazilian Digital Terrestrial TV System (SBTVD), with the participation of researchers from academia and industry. There was a Call for Proposals for this development, resulting in 36 responses from 21 organizations worldwide. The proposals were evaluated and examined, and the SBTVD Forum forwarded its recommendations on selecting candidate technologies to the Brazilian Ministry of Communications. Currently, researchers are working on elaborating specifications for video encoding, audio encoding, and subtitles. This work analyzed the accessibility requirements for subtitles, glosses, and audio description media. Solutions were presented for their implementation by proposing an extension to the CCWS server API and a system architecture, which was implemented as a proof of concept.